Essential oils prepared in Nano-emulsion form for the formulation of cosmetic products. - Medina Calderón, Favio Armando; Bautista Barrios, Luis Carlos (Revista Colombiana de Investigaciones Agroindustriales, 2015)
In this study, essential oils with reported antimicrobial activity, (Origanum, Chamomile, Thymus and lemongrass) were employed to obtain Nano-emulsions, using a low energy technique, evaluating different relations of surfactant/oil ratio (1.5:1; 2:1; 2.5:1 and 3:1) and different NaCl concentrations within the aqueous phase(0.01M, 0.1M and 0.5M). The formulations that obtained nano-emulsions were characterized through atomic force microscopy and were incorporated in different cosmetic formulations (antibacterial gel and moisturizing cream) to evaluate the size of the droplet, the antimicrobial activity and the capacity they have to act as conservation agents. The origanum nano-emulsion evidenced the smallest droplet sizes and a significantly higher antimicrobial activity and conservation capacity than the control formulations (product without Nano-emulsions and with pure essential oil) when it was incorporated in cosmetic formulations. Para citar este artículo Medina, F. y Bautista, L. (2015). Aceites esenciales preparados en forma de nanoemulsión para la formulación de productos cosméticos. Revista colombiana de investigaciones agroindustriales, 2(1), 6-15. DOI: http://dx.doi.org/10.23850/24220582.177